2016
DOI: 10.1039/c6ob01468b
|View full text |Cite
|
Sign up to set email alerts
|

Silver & gold-catalyzed routes to furans and benzofurans

Abstract: Silver and gold have become incredibly versatile and mild catalysts for numerous transformations, especially in heterocycle synthesis. For the most prominent of them, i.e. furans, silver and gold, with their unique reactivity and mildness, allow numerous possible routes to highly substituted and/or functionalized furans from a large variety of starting materials. Silver and gold catalysis provide thus the most flexible way to this important family of compounds. The present review describes these silver and gol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
43
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 99 publications
(43 citation statements)
references
References 157 publications
0
43
0
Order By: Relevance
“…We used two different bases instead of quinine, Et 3 N and Cs 2 CO 3 , and they also led to a mixture of 3a and 4a (Table , Entries 4 and 5). Next, we observed that the reaction occurred between α‐cyano α,β‐unsaturated ketone 1a and ethyl isocyanoacetate ( 2a ) even in the absence of any base, but the product was exclusively the tetrasubstituted furan (Table , Entries 6–8) The reaction proceeded at ambient temperature in MeOH to afford the product in 92 % yield. The yield was further improved to 97 % by using 1,2‐dichloroethane (DCE) as the solvent at an elevated temperature (50 °C).…”
Section: Resultsmentioning
confidence: 97%
“…We used two different bases instead of quinine, Et 3 N and Cs 2 CO 3 , and they also led to a mixture of 3a and 4a (Table , Entries 4 and 5). Next, we observed that the reaction occurred between α‐cyano α,β‐unsaturated ketone 1a and ethyl isocyanoacetate ( 2a ) even in the absence of any base, but the product was exclusively the tetrasubstituted furan (Table , Entries 6–8) The reaction proceeded at ambient temperature in MeOH to afford the product in 92 % yield. The yield was further improved to 97 % by using 1,2‐dichloroethane (DCE) as the solvent at an elevated temperature (50 °C).…”
Section: Resultsmentioning
confidence: 97%
“…Therefore, the efficient synthesis of the benzo[ b ]furan framework continues to attract much interest from synthetic organic chemists. Many transition metal‐assisted synthetic approaches, such as Cu, Au, Pd, Pt, Zn, Ag, and Ru, to the benzo[ b ]furans have been extensively studied and well documented . Among the transition‐metal catalysts, gold salts have emerged as powerful catalysts in recent decades owing to their high catalytic activity and high chemoselectivity for the electrophilic activation of alkynes toward various nucleophiles .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, 2-arylbenzo[ b ]furans were conveniently synthesized by the one-pot tandem Hiyama alkynylation/cyclization reaction between 2-iodophenol and (triethoxysilyl)alkynes [20]. In recent years silver and gold salts have found application as versatile and mild catalysts to access the benzo[ b ]furan ring system through intramolecular cyclization of 2-alkynylphenol substrates [21], including preparation of 2-benzofuranmethanamines [22] and 4-indolylbenzo[ b ]furans [23] in the presence of AgNO 3 and AgOTf, respectively, and 2-phenylbenzo[ b ]furans, where AuCl 3 or a mixture thereof with AgOTf has been used to promote the appropriate cyclization [24].…”
Section: Introductionmentioning
confidence: 99%